ANALISIS KESALAHAN SISWA SEKOLAH DASAR DALAM MENYELESAIKAN MASALAH MATEMATIKA BERDASARKAN NEWMAN - Rissa Prima Kurniawati; Fida Rahmantika Hadi (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Many students in elementary school make mistakes when solving math problems, especially misconceptions. This is caused by a lack of mathematical material understanding, students are lazy to open mathematics books or notes, and students are lazy to do assignments given by the teacher. This study aims to analyze the mistakes of fifth grade elementary school students in solving HOTS math’s problems based on Newman. This type of research in this research is qualitative research. The data collection techniques include tests, interviews, and documentation. Data analysis techniques in this study were data reduction, data presentation, and conclusion drawing. Based on the results of the study, the mistakes made by fifth grade students of SDN 02 Mojorejo Kota Madiun were reading errors, comprehension errors, transformation errors, process skill errors, and answer errors. end (encoding error). The most frequent mistakes made were misunderstanding and process skills errors. Some of the factors that cause students to make mistakes are students who are not familiar with HOTS math problems, students do not write down what is known and asked from the questions, lack of mastery on the material of volume shapes, and students are not careful in answering math questions